Vascular Factors in Patients with Midlife Sensorineural Hearing Loss and the Progression to Mild Cognitive Impairment - Del Vecchio, Valeria; Tricarico, Laura; Pisani, Anna; Serra, Nicola; D’Errico, Domenico; De Corso, Eugenio; Rea, Teresa; Picciotti, Pasqualina M.; Laria, Carla; Manna, Giuseppe; Franzè, Annamaria; Malesci, Rita; et al. (Medicina (Kaunas, Lithuania), 2023)
Background and Objectives: Midlife hearing loss (HL) has been considered as a major modifiable risk factor for a later-life progression to dementia. Our aim was to detect a link between precocious sensorineural hearing loss (SNHL) and mild cognitive impairment (MCI) and their association to putative risk factors for a common pathology. Materials and methods: In this study, a retrospective case-control study was carried out. A total of 112 patients were enrolled as following: 81 patients with bilateral SNHL and 31 subjects with normal hearing, whose ages ranged from 50 to 65 years. Both groups performed pure tone audiometry, a tinnitus handicap inventory (THI), Mini-Mental State examination (MMSE), and the Montreal Cognitive Assessment (MoCA), Hospital Anxiety and Depression Scale (HADS-A and HADS-D). Results: The mean age was 58 ± 5.2 in SNHL patients and 53.2 ± 4.8 in the control group. The mean pure tone average in the SNHL group was 40.2 ± 18.7 dB HL on the right side and 41.2 ± 17.2 dB HL on the left side, while in the control group it was 12.5 ± 2.8 dB HL on right side and 12.4 ± 3.1 dB HL on left side. About 64% of patients with SNHL exhibited comorbidities, and the most common condition was hypertension. Altered MoCA test scores were significantly related to the pure tone averages in patients with SNHL compared to the control group (p = 0.0004), while the differences in the HADS-A and HADS-D were not significant. Furthermore, a significant correlation was observed in SNHL patients between an altered MoCA test and hypercholesterolemia (p = 0.043). Conclusions: Hearing impairment and screening tests to detect MCI should be considered in the midlife in order to carry out strategies to prevent the progression to dementia. Hypertension and hypercholesterolemia are two risk factors in the development of endothelial dysfunction, oxidative stress, and vascular inflammation, and may represent the common pathology linking the inner ear and brain damage.